Studien über europäische Eulophidae, III: Euderinae (Hymenoptera: Chalcidoidea). - Bouček, Zdenĕk (Contributions to Entomology = Beiträge zur Entomologie, 1963)
As the third part of his studies of European Eulophidae (for pts. 1 and 2 see: Acta ent. Mus. natl. Pragae, 33, 117-194, 1959) the author revises the European species of Euderinae. Fifteen valid species and one doubtful species are reviewed, including four species described as new, viz. Euderus agrili, E. brevicornis, Secodelloidea grangeri and Astiehus tauricus. Also one new genus [Euderastichus, for Euderus obscurus THOMS.) and one new subgenus (Linastichus, for Astiehus longevittatus Masi and A. pulchrilineatus Gahan) are described. Several names are sunken in synonymy. Nomenclatural Acts almus Erdös, 1951 (Allocerastichus), syn. n. of Euderastichus obscurus (Thomson, 1878) Linastichus Förster, 1856 (Astichus), sgen. n. tauricus Bouček, 1963 (Astichus (Astichus)), spec. n. amphis Walker, 1839 (Entedon), syn. n. of Euderus albitarsis (Zetterstedt, 1838) mithras Walker, 1839 (Entedon), syn. n. of Euderus albitarsis (Zetterstedt, 1838) obscurus (Thomson, 1878) (Euderastichus), comb. n. hitherto Euderus obscurus Thomson, 1878 agrili Bouček, 1963 (Euderus), spec. n. brevicornis Bouček, 1963 (Euderus), spec. n. viridis Thomson, 1878 (Euderus), syn. n. of Euderus albitarsis (Zetterstedt, 1838) Euderastichus Bouček, 1963 (Eulophidae), gen. n. Stipaebia Erdös, 1954 (Eulophidae), syn. n. of Allosterastichus Masi, 1923 grangeri Bouček, 1963 (Secodelloidea), spec. n.